2015
DOI: 10.1074/jbc.m114.606665
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model of Weak Binding Actomyosin in the Prepowerstroke State

Abstract: Background: Actomyosin generates mechanical force in all eukaryotic cells including muscle. Results: By dynamic computational simulations we revealed structural rearrangements in myosin upon actin binding, leading to the initial state of force generation. Conclusion:The actin binding-induced structural rearrangements in myosin are transmitted specifically through the activation loop of the myosin. Significance: The first actomyosin atomic structural model of the initial state of force generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The activation loop (I1634-G1640) preceding the HLH motif has been suggested to activate myosins through contacts with actin’s negatively charged N terminus (Varkuti et al, 2012; Varkuti et al, 2015). Indeed, K1637 forms a possible salt bridge with subunit i + 2 residue 4E, partially stabilizing actin’s flexible N terminus (Figure S4C).…”
Section: Resultsmentioning
confidence: 99%
“…The activation loop (I1634-G1640) preceding the HLH motif has been suggested to activate myosins through contacts with actin’s negatively charged N terminus (Varkuti et al, 2012; Varkuti et al, 2015). Indeed, K1637 forms a possible salt bridge with subunit i + 2 residue 4E, partially stabilizing actin’s flexible N terminus (Figure S4C).…”
Section: Resultsmentioning
confidence: 99%
“…It has been revealed by experiments involving actin and a myosin head (myosin subfragment S1) that the enthalpic and entropic components of the binding free energy are both positive, irrespective of the presence of a nucleotide (4,5), which implies that the binding is entropically driven. By contrast, several results from molecular dynamics (MD) simulations have suggested that the binding is energetically driven (6)(7)(8). Lorenz and Holmes have obtained an atomic structural model of rigor (strong)-binding actomyosin using an MD simulation based on an electron microscopy map of the actomyosin complex and the crystal structures of actin and myosin monomers (6).…”
Section: Introductionmentioning
confidence: 99%
“…Okazaki et al performed in silico titration by employing a coarse-grained actomyosin model with the Debye-Hu ¨ckel solvent model (7) and claimed that the binding is driven by actin-myosin electrostatic attractive interaction. Va ´rkuti et al calculated the binding free energy using the molecular mechanics Poisson-Boltzmann surface area method (8). Their results also indicate that salt bridges and hydrogen bonds between actin and myosin play important roles in the binding.…”
Section: Introductionmentioning
confidence: 99%
“…Arg232 has been discussed earlier to play a critical role for myosin function through a complex salt-bridge found in a scallop myosin crystal structure [ 44 ], and this is consistent with studies suggesting particular arginine residues to serve as key connectors between functional subunits in proteins [ 50 ]. In conclusion, our structural and computational study sheds light on a new myosin conformation and the two-step mechanism of the force-generating myosin power stroke, providing molecular insights into the potential conformational transitions associated with ADP release, thereby contributing to recent progress [ 24 , 25 , 26 , 31 , 51 ] in resolving the mechanism of force production and cellular motility by molecular motors.…”
Section: Discussionmentioning
confidence: 85%
“…The power stroke is initiated by ATP hydrolysis, followed by reattachment of the myosin motor in the pre-power stroke state to its actin filament track, coupled to conformational changes that finally lead to the release of the hydrolysis products and to force generation. The exact sequence of events is critically discussed in the field, and several models have been proposed for the conformational states involved in the power stroke [ 24 , 25 , 26 , 27 ]. The conformational changes required for force production are assumed to be driven by actin reattachment and the sequential release of inorganic phosphate (P i ), Mg 2+ , and adenosine diphosphate (ADP).…”
Section: Introductionmentioning
confidence: 99%